IL-21–Deficient T Follicular Helper Cells Support B Cell Responses Through IL-27 in Patients With Chronic Hepatitis B - Khanam, Arshi; Ayithan, Natarajan; Tang, Lydia; Poonia, Bhawna; Kottilil, Shyam (Frontiers in Immunology, 2021)
Chronic Hepatitis B (CHB) affects over 350 million people worldwide. Current treatment does result in reduced complications; however, a cure (development of antibodies to the S antigen) is not achieved, requiring life-long therapy. Humoral responses contribute to viral elimination by secreting neutralizing antibodies; though, effective induction of humoral immunity require CD4T cell differentiation into T follicular helper (TFH) cells that support B cell response through interleukin-21 (IL-21). In CHB, mechanism of TFH-B interactions is seldom described. During CHB, TFH cells are defective in producing IL-21 in response to hepatitis B surface antigen (HBsAg). However, regardless of low IL-21, TFH cells efficiently support B cell responses by producing interleukin-27 (IL-27), which directs the formation of plasmablasts and plasma cells from memory and naïve B cells by enhancing B lymphocyte-induced maturation protein-1. IL-27 not only improved total antibody production but HBsAg-specific IgG and IgM secretion that are essential for viral clearance. Importantly, IL-27+TFH cells were significantly associated with HBV DNA reduction. Therefore, these findings imply a novel mechanism of TFH mediated B cell help in CHB and suggest that IL-27 effectively compensate the function of IL-21 by supporting TFH-B cell function, required for protective antibody response and may contribute to viral clearance by providing potential target for achieving a functional cure.